BLAST: A short computerized test to measure the ability to stay on task. Normative behavioral data and detailed cortical dynamics. (November 2019) - Petton, Mathilde; Perrone-Bertolotti, Marcela; Mac-Auliffe, Diego; Bertrand, Olivier; Aguera, Pierre-Emmanuel; Sipp, Florian; Batthacharjee, Manik; Isnard, Jean; Minotti, Lorella; Rheims, Sylvain; Kahane, Philippe; Herbillon, Vania; et al.
Abstract: This article provides an exhaustive description of a new short computerized test to assess on a second-to-second basis the ability of individuals to « stay on task », that is, to apply selectively and repeatedly task-relevant cognitive processes. The task (Bron/Lyon Attention Stability Test, or BLAST) lasts around 1 min, and measures repeatedly the time to find a target letter in a two-by-two letter array, with an update of all letters every new trial across thirty trials. Several innovative psychometric measures of attention stability are proposed based on the instantaneous fluctuations of reaction times throughout the task, and normative data stratified over a wide range of age are provided by a large (>6000) dataset of participants aged 8 to 70. We also detail the large-scale brain dynamics supporting the task from an in-depth study of 32 participants with direct electrophysiological cortical recordings (intracranial EEG) to prove that BLAST involves critically large-scale executive attention networks, with a marked activation of the dorsal attention network and a deactivation of the default-mode network. Accordingly, we show that BLAST performance correlates with scores established by ADHD-questionnaires. Highlights: a short (2-mn) computerized task to track the ability to « stay continuously on task » on a second-to-second basis: BLAST. New behavioral indices of attention based on the instantaneous variability of reaction times. Detailed description of the cortical networks dynamics supporting optimal attention during BLAST.